Current Understanding of the Structure and Function of Fungal Immunomodulatory Proteins - Liu, Yusi; Bastiaan-Net, Shanna; Wichers, Harry J. (Frontiers in Nutrition, 2020)
Fungal immunomodulatory proteins (FIPs) are a group of proteins found in fungi, which are extensively studied for their immunomodulatory activity. Currently, more than 35 types of FIPs have been described. Based on their conserved structure and protein identity, FIPs can be classified into five subgroups: Fve-type FIPs (Pfam PF09259), Cerato-type FIPs (Pfam PF07249), PCP-like FIPs, TFP-like FIPs, and unclassified FIPs. Among the five subgroups, Fve-type FIPs are the most studied for their hemagglutinating, immunomodulating, and anti-cancer properties. In general, these small proteins consist of 110-125 amino acids, with a molecular weight of ~13kDa. The other four subgroups are relatively less studied, but also show a noticeable influence on immune cells. In this review, we summarized the protein modifications, 3-dimensional structures and bioactivities of all types of FIPs, and discuss their structure-function relationships, to gain a comprehensive understanding of FIPs’ working mechanisms and scope further studies.